(untitled) (Research, Society and Development, 2020)
In the face of the difficulties and potentialities of the indigenous communities of the Xakriabá Reserve, the Programa de Educação Tutorial - PET Agronomia and PET Conexões de Saberes – Indígena, organizes a field day every year, leading training to the indigenous community and promoting cultural exchange between traditional populations and the university. The extension action has been carried out since 2015 and in 2019 it had its fifth edition. The activities occurred in schools of Santa Cruz, Itapicuru and Rancharia villages with participants from different villages of the Reserve. The objective is to promote simple workshops, using the resources available to the community, without depending on electronic equipment or materials that are difficult to access. The target audience of the activities is composed of children, youth, adults and elderly, indigenous men and women, including leaders and professionals such as teachers and healthcare agents. The community has great participation and involvement in the activities, with answers to questions, observations and the daily application of the workshops, as well as in hosting students. At the university there is the involvement of the undergraduate and graduate courses of the ICA/UFMG and indigenous students by giving back to their origins the technical knowledge acquired. The action allows the exchange of experiences with the community, improvement of the students in extension and citizenship, taking the knowledge to the non-academic public.